Extrastriatal dopamine D2/3 receptors and cortical grey matter volumes in antipsychotic-naïve schizophrenia patients before and after initial antipsychotic treatment. (3rd October 2017) - Nørbak-Emig, Henrik; Pinborg, Lars H.; Raghava, Jayachandra M.; Svarer, Claus; Baaré, William F.C.; Allerup, Peter; Friberg, Lars; Rostrup, Egill; Glenthøj, Birte; Ebdrup, Bjørn H.
Abstract: Objectives: Long-term dopamine D2/3 receptor blockade, common to all antipsychotics, may underlie progressive brain volume changes observed in patients with chronic schizophrenia. In the present study, we examined associations between cortical volume changes and extrastriatal dopamine D2/3 receptor binding potentials (BPND ) in first-episode schizophrenia patents at baseline and after antipsychotic treatment. Methods: Twenty-two initially antipsychotic-naïve patients underwent magnetic resonance imaging (MRI), [ 123 I]epidepride single-photon emission computerised tomography (SPECT), and psychopathology assessments before and after 3 months of treatment with either risperidone ( N = 13) or zuclopenthixol ( N = 9). Twenty healthy controls matched on age, gender and parental socioeconomic status underwent baseline MRI and SPECT. Results: Neither extrastriatal D2/3 receptor BPND at baseline, nor blockade at follow-up, was related to regional cortical volume changes. In post-hoc analyses excluding three patients with cannabis use we found that higher D2/3 receptor occupancy was significantly associated with an increase in right frontal grey matter volume. Conclusions: The present data do not support an association between extrastriatal D2/3 receptor blockade and extrastriatal grey matter loss in the early phases of schizophrenia. Although inconclusive, our exclusion of patients tested positive for cannabis use speaks to keeping attention to potential confounding factors in imaging studies.